A STUDY ON THE IMPACT OF BEHAVIORAL BIASES ON INVESTMENT DECISIONS OF RISK SEEKING INVESTORS IN INDIA - Mohapatra, A. K.Das; Samal, Anuradha (International Journal of Psychosocial Rehabilitation, 2020)
In the past two and half decade a paradigm shift has taken place in the field of financial economics from standard finance to a new field of finance named as Behavioral Finance. Behavioral Finance enriches the standard finance theories or models by giving insights from psychology, neuroscience, sociology, organisation behaviour and law and explains how the cognitive errors and emotions of investors influences their decision making process. Behavioral Finance is an emerging field that combines the understanding of behavioural and cognitive psychology with financial decision making process. It is the fastest growing area in the field of academic research in finance. This investigates whether behavioral biases are evident among Indian risk seeking Investors or not and which bias is most prominent among risk seeking investors.